Fetal programming through early weaning shapes the metabotype of Nelore heifers - Anjaleena Yaseen; Ana Laura dos Santos Munhoz Gôngora; Thiago Kan Nishimura; Gabriel Henrique Ribeiro; Eduardo Solano Pina Santos; Alanne Tenório Nunes; Tarique Hussain; Amjad Hameed; Luiz Alberto Colnago; Paulo Roberto Leme; Arlindo Saran Netto; Guilherme Pugliesi; et al. (PLoS ONE, 2025)
This study investigated the effects of fetal programming induced by early weaning (EW) of the previous calf on the serum metabotype of Nelore heifers. A 2 × 2 factorial design was employed, considering maternal category (multiparous vs. second-parity) and weaning strategy [EW vs. conventional weaning (CW)]. A total of 55 heifers were evaluated, including 25 born to cows subjected to EW (15 multiparous, 10 second-parity) and 30 born to cows subjected to CW (15 multiparous, 15 second-parity). Serum samples were collected from heifers at an average age of 14 months prior to the initiation pf the fixed-time artificial insemination (FTAI) protocol, and metabolomic profiling was conducted using ¹H-NMR spectroscopy. Data analysis was performed using R software and MetaboAnalyst 6.0. The effects of weaning strategy and maternal category were assessed through partial least squares-discriminant analysis (PLS-DA) and differential abundance analysis, while enrichment analysis was applied to identify biological pathways associated with the observed metabolic changes. The results demonstrated significant effects of weaning strategy, maternal category, and their interaction on the serum metabotype. Heifers born to second-parity cows subjected to EW exhibited elevated concentrations of glutamate, acetate, citrate, and hippurate compared to those subjected to CW, whereas no significant differences between weaning strategies were observed in heifers born to multiparous cows. Weaning strategies modulated metabolic pathways related to energy metabolism, amino acid utilization, and gluconeogenesis. Furthermore, heifers born to multiparous cows displayed higher serum levels of phenylalanine, creatine phosphate, and glutamine, indicating enhanced nutrient availability for growth, development, and metabolic programming compared to their counterparts born to second-parity cows. These findings underscore the potential of EW to improve metabolic efficiency and nutrient reallocation, particularly under conditions of limited feed availability or heightened physiological demands. Overall, this study offers valuable insights into the metabolic programming of beef cattle, supporting strategies to optimize weaning protocols and enhance productivity in cattle production systems.